Kurikulum Merdeka Belajar pada Mata Pelajaran Pendidikan Agama Islam di SMP Muhammadiyah Besitang - Syahfitria Lestari; Zaifatur Ridha; Usmaidar Usmaidar (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The independent learning curriculum is a new curriculum in schools that requires schools to adapt in its implementation and will not be free from problems. This research aims to describe the planning, implementation and evaluation of the implementation of the Independent Learning Curriculum in Islamic religious education subjects at the Besitang Muhammadiyah Private Middle School. This type of research is field research using descriptive qualitative methods. The data collection techniques used were observation, interviews and documentation. The results of the research are that the implementation of the Independent Learning Curriculum, especially in Islamic Religious Education subjects at the Besitang Muhammadiyah Private Middle School, has gone quite well, although there are still many improvements because various related parties are still in the process of adjusting. The implementation of the Merdeka Belajar Curriculum in Islamic religious education subjects at the Muhammadiyah Besitang Private Middle School has obstacles which include, a lack of supplies of facilities and infrastructure, as well as training to implement the Merdeka Belajar Curriculum for Islamic religious education teachers, which is the cause of the lack of implementation of the Merdeka Belajar Curriculum in Islamic religious education subjects. maximum. Despite this, Besitang Muhammadiyah Private Middle School will continue to improve. Besitang Muhammadiyah Private Middle School has carried out P5 activities (project to strengthen the profile of Pancasila students) and has produced products from P5. Evaluation of independent curriculum-based learning uses formative and summative assessments.